Postural Control and Balance in Ankylosing Spondylitis - Tulay Yildirim; Oguzhan Yildirim (Medicine Science, 2015)
Ankylosing spondylitis (AS) is a chronic inflammatory disease characterised by inflammatory back pain and the formation of syndesmophytes which lead to ankylosis. Postural deviation in AS patients is caused by increased thoracic kyphosis and hip flexion which then causes the centre of body weight to shift anteriorally. As a compensation mechanism, knee flexion and plantar flexion develop. Although it has been estimated that the typical deformities which occur may have a negative effect on postural balance, there are very few studies on this subject and contradictory results have been obtained. In this study, it was aimed to evaluate the changes in the musculoskeletal system of AS patients and to examine the effects of these on postural control and balance. [Med-Science 2015; 4(1.000): 2057-64]